PENGARUH TIME BUDGET PRESSURE, INDEPENDENCE, LOCUS OF CONTROL TERHADAP DYSFUNCTIONAL AUDIT BEHAVIOR - Nabila Rizka Fatiha, (2023)
This study aims to analyze how Time Budget Pressure, Independence, and Locus of Control affect dysfunctional audits. This research is a quantitative research with primary data types using a questionnaire and a Likert scale as a measuring tool. Data analysis using multiple linear regression. The population in this study are auditors who work for KAPs in the city of Jakarta. Determination of the sample in this study using purposive sampling method. The samples obtained in this study amounted to 140 auditors, but only 106 could be processed in 24 KAPs in DKI Jakarta. The method used is the Structural Equation Model (SEM). The results obtained in this study are Time budget pressure has no effect on Dysfunctional Audit, Independence has a negative effect on Dysfunctional Audit, Locus of Control Internal has no effect on Dysfunctional Audit and Locus of Control External has a negative effect on Dysfunctional Audit. Future researchers are expected to change the independent variable in the next study.